2021
DOI: 10.3390/atmos12070900
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Power Plant NOx Emissions over Northwest Greece Using a Data Assimilation Technique

Abstract: In this work, we investigate the ability of a data assimilation technique and space-borne observations to quantify and monitor changes in nitrogen oxides (NOx) emissions over Northwestern Greece for the summers of 2018 and 2019. In this region, four lignite-burning power plants are located. The data assimilation technique, based on the Ensemble Kalman Filter method, is employed to combine space-borne atmospheric observations from the high spatial resolution Sentinel-5 Precursor (S5P) Tropospheric Monitoring In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This work can be extended to generate a top-down emission inventory using the TROPOMI observations and data assimilation based on the LOTOS-EUROS. This technique has already been demonstrated successfully over point NOx emission sources [37]. The clear separation of maritime traffic in well-defined lanes crossing the Mediterranean Seas demonstrated in this work will allow us to apply the same data assimilation technique to update marine pollution-related emissions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This work can be extended to generate a top-down emission inventory using the TROPOMI observations and data assimilation based on the LOTOS-EUROS. This technique has already been demonstrated successfully over point NOx emission sources [37]. The clear separation of maritime traffic in well-defined lanes crossing the Mediterranean Seas demonstrated in this work will allow us to apply the same data assimilation technique to update marine pollution-related emissions.…”
Section: Discussionmentioning
confidence: 73%
“…More specifically, a recent analysis studying the sensitivity of the OMI observed NO 2 columns to anthropogenic emissions concluded that the contribution of the increasing shipping emissions in adjacent areas may mask a significant part of national emission reductions [35]. An evaluation of the model performance over Greece was recently conducted while, over high emitting locations such as power plants, the modelled columns were found to be highly spatially correlated (R = 0.95) with the TROPOMI tropospheric columns [36,37]. LOTOS-EUROS NO 2 simulations were also performed in order to quantify the effects of the lockdown due to the COVID-19 pandemic over Greece as observed by TROPOMI [27].…”
Section: The Lotos-euros Ctm Simulationsmentioning
confidence: 99%
“…A model evaluation against ground-based measurements over two major Greek cities has shown that the modelled NO2 surface concentrations show a high spatial correlation of 0.86 and a moderate underestimation of about 10% [33]. When compared to industrial stations located near power plants in Greece, LOTOS-EUROS NO2 surface concentrations mean seasonal bias improves to 2 μg/m 3 from 10 μg/m 3 , after assimilating the space-borne TROPOMI NO2 observations [34]. The model has also been recently used to estimate changes in NO2 emissions due to the COVID-19 pandemic restrictive measures [26] and to study NO2 concentrations attributed to shipping activity in the Mediterranean and the Black Sea basin [35].…”
Section: Lotos-euros Ctm Simulationsmentioning
confidence: 99%
“…The model profile is convoluted with these averaging kernels, provided in the satellite download data product to simulate the retrieval for a correct model and satellite retrieval products comparison [48]. The averaging kernels are implemented to the model output at the time of the nearest satellite overpass, which is usually at 18:30 UTC [49]. A selection on the pixel quality flag (qa) was been applied, averaging over the pixels filtered for (qa) > 0.55.…”
Section: Lotos-euros Simulationsmentioning
confidence: 99%
“…Different works have studied the effect of assimilation of satellite retrieved NO 2 data on emissions or Surface concentrations in a global domain [57,60] pointing towards the ability to estimate emissions by assimilating satellite observations that are taken only once per day over one place concerning with the NO 2 atmospheric life time during different times of the year. On another side regional domain estimation studies like Skoulidou et al [49], Wang et al [61] orient our subsequent emission experiments toward the interest of persistent emission estimation capabilities.…”
Section: Impact Over Major Citiesmentioning
confidence: 99%